2012
DOI: 10.1007/s10461-012-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Relationship Power and Malnutrition Among HIV-Positive Women in Rural Uganda

Abstract: Inequality within partner relationships is associated with HIV acquisition and gender violence, but little is known about more pervasive effects on women’s health. We performed a cross-sectional analysis of associations between sexual relationship power and nutritional status among women in Uganda. Participants completed questionnaires and anthropometric measurements. We assessed sexual relationship power using the Sexual Relationship Power Scale (SRPS). We performed logistic regression to test for association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…We also found that RC (i.e., relationship control) was more strongly correlated with sexual violence than DMD (i.e., decision-making dominance), which is consistent with a study of malnutrition among HIV-positive women from Uganda [41] and other research describing sexual violence as an attempt by men to maintain control over female partners (e.g., [22, 58, 59]). This finding may also be related to the psychometric properties of the RC subscale.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that RC (i.e., relationship control) was more strongly correlated with sexual violence than DMD (i.e., decision-making dominance), which is consistent with a study of malnutrition among HIV-positive women from Uganda [41] and other research describing sexual violence as an attempt by men to maintain control over female partners (e.g., [22, 58, 59]). This finding may also be related to the psychometric properties of the RC subscale.…”
Section: Discussionsupporting
confidence: 91%
“…Little research has examined this association among entire samples of HIV-positive women, who have higher rates of violence and poverty than their HIV-negative counterparts [36–38] and are highly susceptible to stigma, discrimination, and poor physical and mental health as a consequence of their HIV status [3941]. These co-occurring epidemics of psychosocial problems, often termed syndemics [42], may interact in ways that synergistically worsen health disparities between HIV-positive and negative individuals [43, 44], with the potential to further spread the HIV virus to children and men.…”
Section: Introductionmentioning
confidence: 99%
“…Gender-based power imbalances within sexual relationships can negatively affect women’s sexual, reproductive, physical, and mental health (Blanc, 2001; Hatcher et al, 2012; McMahon et al, 2015; Siedner et al, 2012; Wingood & DiClemente, 2002). According to the theory of gender and power (TGP), there are three social structures that interact at the societal and institutional levels to influence health: economic inequalities (the division of labor), male partner control (the division of power), and social norms and affective attachments around gender (Connell, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Second, analyses of data collected from samples of non-HIV-infected persons have linked powerlessness to depression among women experiencing intimate partner violence [27], [31], and among young women [27], [29]. Studies have found other negative health impacts of low sexual power among HIV-infected women, including malnutrition and worse HIV treatment outcomes [32], [33].…”
Section: Introductionmentioning
confidence: 99%